Job Demands, Resources and Burnout Among Polish Nurses During the Late Wave of COVID-19 Pandemic: The Mediating Role of Emotional Labor - Wójcik, Grzegorz; Wontorczyk, Antoni; Barańska, Ilona (Frontiers in Psychiatry, 2022)
Objective: Burnout has been recognized as a serious health problem. Nurses as a professional group are at a high risk of burnout occurrence, especially when facing burden associated with the COVID-19 pandemic. Despite evidence that higher job demands lead to burnout, there is less known about the indirect effect of job demands and resources on burnout via surface acting. Using the JD-R framework, this study examined how job demands and resources affected burnout among Polish nurses and whether these relationships are mediated by surface acting and moderated by coping with the workload. Methods: A sample of 270 nurses from the biggest hospital in Southern Poland filled out an online questionnaire at the time between the fourth and the fifth wave of the COVID-19 pandemic pandemic in Poland. The Polish adaptations of Oldenburg Burnout Inventory (OLBI), Organizational Constraints Scale (OCS), Interpersonal Conflict at Work (ICAWS), Areas of Worklife Survey (AWS) and Emotional Labour Scale (ELS) were used. Mediation and moderation analyses were carried out in the SPSS macro-PROCESS. Results: Surface acting partially mediated the positive association between organizational constraints and interpersonal conflict at work and burnout, as well as the negative association between the perceived organizational support and burnout. Coping with workload moderated the direct effect of organizational constraints on burnout via surface acting. Conclusions: The findings enrich the knowledge of the mediating and moderating mechanisms to explain the association between job demands, resources and burnout among nurses. There have been proposed interventions concerning increasing organizational support, effective emotional regulation of management education and psychological training regarding adequate coping strategies which could help reduce or prevent the occurrence of burnout in this professional group.